12x-8<2x-6-8<-6x∈(-∞;∞)2x²-4x>-3x²-4x+3>0x1+x2=4 U x1*x2=3⇒x1=1 U x2=3x∈(-∞;1) U (3;∞)3(1/5)^(3x+4)*(1+1/5)>6(1/5)^(3x+4)>53x+4<-13x<-5x<-5/3x∈(-∞;-5/3)42^x=a2a²-5a+2≥0D=25-16=9a1=(5-3)/4=1/2a2=(5+3)/4=2a≤1/2⇒2^x≤1/2⇒x≤-1a≥2⇒2^x≥2⇒x≥1x∈(-∞;-1] U [1;∞)5x<0log(1/3)(x/(2x-4))>0x/(2x-4)<1(x-2x+4)/(2x-4)<0(x-4)/2(x-2)>0x=4 U x=2x<2 U x>4 U x<0x∈(-∞;0)6x>0log(0,3)((x²+22)/13x)<0(x²+22)/13x>1(x²+22-13x)/13x>0x1+x2=13 U x1*x2=22⇒x1=2 U x2=1113x=0⇒x=0 _ + _ +-----------(0)-----(2)--------(11)----------x∈(0;2) U (11;∞)7x>0 U x<4log(1/3)(4x-x²)>-14x-x²<3x²-4x+3>0x1=x2=4 u x1*x2=3⇒x1=1 U x2=3x<1 U x>3x∈(0;1) U (3;4)8log(5)x=a2a²+5a+5≥0D=25-16=9a1=(-5-3)/4=-2a2=(-5+3)/4=-1/2a≤-2⇒log(5)x≤-2⇒x≤1/25a≥-1/2⇒log(5)x≥-1/2⇒x≥1/√5x∈(0;1/15) U (1/√5;∞)